63:oral Health technology assessment as part of a broader process for priority setting and resource allocation. (28th April 2022) - Mitton, Craig; Seixas, Brayan; Peacock, Stuart; Burgess, Michael; Bryan, Stirling
Abstract : Over the last two decades, economic evaluation of health technologies has developed enormously, affirming its importance within the pursuit of efficiency in the management of health care systems. One concern that has been raised with health technology assessment (HTA) has been its impact on decision making. A key aspect of this has been the pursuit of increasingly sophisticated modelling and technical details at the expense of an oftentimes lack of appreciation of how decisions are made in practice. Here we suggest a mechanism by which HTA can be understood as an input into a broader framework for priority setting and resource allocation. This paper starts with a brief introduction to what HTA is and how it can be robustly applied within the context of a Canadian provincial Ministry of Health process for assessing new technologies. Limitations of the impact of HTA specifically as a 'one-off' assessment process are identified and in response a framework is put forward clearly outlining how HTA can fit in a broader priority setting framework. The framework enables trade-offs to be made and thereby relies on both assessment of new services as well as reassessment of existing services. In fact, the explicit framework, when applied at the macro level within a health system allows for the broadest trade-offs possible while ensuring the highest quality evidence available at a given time and in a given place is incorporated into the decision making process. In this process the concept of disinvestment is dealt with directly as is the notion of relative value so systems achieve the highest return on investment. In addition, public engagement can be readily disentangled both for the HTA itself as well as in the broader application of the priority setting framework.